Aprovechamiento de la energía geotérmica en El Salvador - Umanzor, Erick; Berdugo, Eduardo; Aguilar, Atilio; Martí, Carlos Miguel; Brizuela, Rubén Salvador (ECA: Estudios Centroamericanos, 1972)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 27, No. 285, 1972: 489-496.